MED10 Drives the Oncogenicity and Refractory Phenotype of Bladder Urothelial Carcinoma Through the Upregulation of hsa-miR-590 - Wu, Chia-Chang; Wang, Yuan-Hung; Hu, Su-Wei; Wu, Wen-Ling; Yeh, Chi-Tai; Bamodu, Oluwaseun Adebayo (Frontiers in Oncology, 2022)
Background: Dysfunctional transcription machinery with associated dysregulated transcription characterize many malignancies. Components of the mediator complex, a principal modulator of transcription, is increasingly implicated in cancer. The mediator complex subunit 10 (MED10), a vital kinase module of the mediator, plays a critical role in bladder physiology and pathology. However, its role in the oncogenicity, metastasis and disease recurrence in bladder cancer (BLCA) remains unclear. Objective: Thus, we investigated the role of dysregulated or aberrantly-expressed MED10 in the enhanced onco-aggression, disease progression, and recurrence of bladder urothelial carcinoma (UC), as well as the underlying molecular mechanism. Methods: Using an array of multi-omics big data analyses of clinicopathological data, in vitro expression profiling and functional assays, and immunocytochemical staining, we assessed the probable roles of MED10 in the progression, and prognosis of BLCA/UC. Results: Our bioinformatics-aided gene expression profiling showed that MED10 is aberrantly expressed in patients with BLCA, is associated with high grade disease, positively correlated with tumor stage and confers significant survival disadvantage. Re-analyzing the TCGA BLCA cohort (n = 454), we showed that aberrantly expressed MED10 expression is associated with metastatic and recurrent disease, disease progression, immune suppression, and therapy failure. Interestingly, we demonstrated that MED10 interacts with and is co-expressed with the microRNA, hsa-miR-590, and that CRISPR-mediated knockout of MED10 elicits downregulation of miR-590 preferentially in metastatic UC cells, compared to their primary tumor peers. More so, silencing MED10 in SW1738 and JMSU1 UC cell lines significantly attenuate their cell proliferation, migration, invasion, clonogenicity, and tumorsphere formation (primary and secondary), with associated downregulation of BCL-xL, MKI67, VIM, SNAI1, OCT4, LIN28A, but upregulated BAX protein expression. In addition, we showed that high MED10 expression is a non-inferior biomarker of urothelial recurrence compared with markers of cancer stemness, however, MED10 is a better biomarker of local recurrence than any of the stemness markers. Conclusion: These data provide preclinical evidence that dysregulated MED10/MIR590 signaling drive onco-aggression, disease progression, and recurrence of bladder UC, and that this oncogenic signal is therapeutically actionable for repressing the metastatic/recurrent phenotypes, enhancing therapy response, and shutting down stemness-driven disease progression and relapse in patients with BLCA/UC.